Revenue Administration : Implementing a High-Wealth Individual Compliance Program - Mc Laughlin, Lucilla (Technical Notes and Manuals; Technical Notes and Manuals ;, 2017)
This technical note is provided as guidance to tax administrations that are considering a program to enhance the tax compliance of high wealth individuals. The note explains the rationale for a specialized compliance program for this segment of the taxpayer base and provides guidance on defining the population of wealthy individuals. Advice is also given on how to assess readiness for such a compliance program, taking into account the legal framework, the political environment, the availability of the necessary data and the administration's capacity to implement it. The note then gives practical advice on implementing a high wealth individual compliance program, using the compliance risk management model as its foundation.